The Role of Vitamin D in Allergic Diseases - Joanna Maria Szydziak; Aleksandra Hrapkowicz; Kinga Janowska; Daria Dąbkowska; Olga Szeidl; Dominika Rehan; Julia Wołoszczak; Agnieszka Mioskowska (Quality in Sport)
Introductions: Vitamin D has gained recognition in recent decades not only as a key regulator of calcium and phosphorus metabolism and bone health but also as an important factor modulating the immune system. Research indicates that vitamin D influences both innate and adaptive immune responses, which is significant in the treatment of allergic and inflammatory diseases. Vitamin D has a beneficial effect on asthma exacerbations and may help reduce respiratory inflammation, as well as alleviate symptoms of allergic rhinitis. Vitamin D deficiency may increase the risk of food allergies, worsen symptoms of atopic dermatitis, and contribute to the transition from acute to chronic urticaria. Conversely, supplementation may help prevent allergies, reduce the severity of atopic dermatitis by supporting skin barrier function and antimicrobial peptide production, and relieve symptoms in patients with chronic urticaria. Purpose of the study: The review article aims to present the current state of knowledge on the role of vitamin D in the treatment of asthma, allergic rhinitis, food allergies, atopic dermatitis, chronic urticaria, and eczema. Material and methods: To summarize the current knowledge on the topic, a literature review of English language papers with a focus on the most current literature was performed. The review was conducted with the PubMed database with 64 works used, accessed before October 2024. Conclusions: Although the impact of blood vitamin D levels on the development and progression of allergic diseases has not yet been fully clarified, scientific studies suggest its significant role in modulating immune responses. Due to its immunoregulatory properties, vitamin D offers new hope for more effective treatment and prevention of allergic diseases.